Moxa floss processing method, cloth and product thereof
By employing a processing method involving substrate pretreatment, water-based composite functional slurry spraying, gradient curing, and post-treatment, the problems of functional dispersion and poor adhesion of moxa wool fabric in specific parts of the human body have been solved, achieving multi-effect synergy and long-term functional release of moxa wool fabric.
Patent Information
- Application Number
- CN202511383441.9
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2025-09-26
- Publication Date
- 2025-11-11
AI Technical Summary
Existing moxa wool fabrics have limited functionality at specific acupoints or parts of the human body, poor adhesion of moxa wool, easy detachment, limited functionality, and difficulty in precisely controlling the production process, resulting in unstable product performance and low retention rate of active ingredients from mugwort leaves.
The process involves substrate pretreatment, water-based composite functional slurry spraying, gradient curing, and post-treatment. A CNC spraying platform is used to achieve precise quantitative spraying of functional moxa wool fabric. Combined with chemical cross-linking and three-dimensional network structure, the permanent fixation and multi-effect synergy of functional fillers are ensured.
It achieves selective enrichment of mugwort floss components in specific parts of the human body and permanent fixation of functional fillers, improving the functional durability of the fabric and the bonding strength of the coating. It has the functions of mugwort active release, far-infrared heat effect and negative ion air purification, and can still maintain more than 80% of the active ingredients after 20 standard washes.
Smart Images

Figure CN120925330A_ABST
Abstract
Description
Technical Field
[0001] This application relates to the field of daily necessities, and more specifically, to a method for processing mugwort floss, fabrics and their products. Background Technology
[0002] Mugwort floss is a type of fleece fabric made from microfiber fleece as the base material. Through a special finishing technique, natural extracts of mugwort are firmly attached to the fibers, resulting in a fleece fabric with a mugwort fragrance and potential calming and soothing health benefits. It is widely used in blankets, loungewear, cushions, eye masks, and other products. While mugwort floss fabric, when combined with other fabrics, possesses certain health benefits, it has significant limitations: First, the uniform distribution of mugwort floss prevents targeted application to specific acupoints or areas of the body, resulting in dispersed efficacy; second, the attachment of mugwort floss is purely physical, leading to poor adhesion, easy shedding and dusting, and poor durability; third, its function is singular, lacking synergistic effects with other functional materials. Furthermore, current production processes for mugwort floss fabric struggle to precisely control the distribution and dosage of functional materials, resulting in unstable product performance. Traditional processing methods also have a low retention rate of active ingredients from mugwort leaves, affecting the product's long-lasting efficacy. In the field of functional textiles, achieving the organic combination of mugwort floss with other functional materials and ensuring its long-term stable efficacy remains a pressing technical challenge. Therefore, existing technologies urgently need improvement to address these issues. Summary of the Invention
[0003] The purpose of this application is to provide a method for processing moxa wool, fabric and its products, which can solve the above-mentioned technical problems.
[0004] This application provides a method for processing mugwort floss, including the following steps: Step 1: Substrate pretreatment: Provide an wormwood blended fabric, and clean, anti-oxidize and perform conventional pretreatment on the fabric to achieve the preset wicking effect and pH value; Step 2, Slurry preparation: Prepare an aqueous composite functional slurry, which includes a composite base material composed of natural plant gum and aqueous synthetic resin, a functional filler containing ultrafine Artemisia argyi extract powder and inorganic functional powder, and processing aids; homogenize it and achieve the predetermined viscosity by a combination of high-speed stirring and ultrasonic dispersion. Step 3, Functional Artemisia argyi fabric spraying: Fix the fabric treated in Step 1 onto the CNC spraying platform, and control the precision nozzle to perform non-contact quantitative spraying on specific areas of the fabric according to the pre-designed digital pattern program, so as to accurately control the amount of slurry deposited per unit area. Step 4, Pre-curing and intermediate treatment: The sprayed fabric is subjected to gradient heating through a multi-temperature zone infrared pre-curing channel to allow the slurry to initially form a film and set. Then, a room temperature rolling process is performed to smooth the fibers and enhance adhesion. Step 5, Final Curing: The intermediate-treated fabric is fully cross-linked and cured in a high-temperature hot air environment, so that the slurry base material forms a three-dimensional network structure to permanently fix the functional filler. Step 6, Post-treatment: The cured fabric is subjected to gentle drying, water-repellent finishing and final molding to obtain functional moxa wool fabric products with enhanced functions.
[0005] Preferably, in step one, the blending ratio of mugwort fibers to natural fibers in the mugwort blended fabric is (50-70) / (50-30). The antioxidant treatment is performed by treating the fabric with a 3-8% citric acid or ascorbic acid solution at 50-70℃ for 20-40 minutes. The fabric after conventional pretreatment has a capillary effect ≥10cm / 30min, a pH value of 6.5-7.5, and a moisture content of less than 10%.
[0006] Preferably, in step two, the dry weight ratio of natural plant gum to waterborne polyurethane resin in the composite base material is (30-50):(70-50). The natural plant gum is selected from one or more of guar gum, xanthan gum, and locust bean gum. The waterborne synthetic resin is selected from one or more of waterborne polyurethane, waterborne acrylic resin, and waterborne epoxy resin. The particle size of the ultrafine Artemisia argyi extract powder in the functional filler is 800-1200 mesh, accounting for 10-20% of the total weight of the slurry. The inorganic functional powder is far-infrared ceramic powder and negative ion mineral powder, with a particle size of nanometer to submicron, accounting for 3-8% of the total weight of the slurry, respectively. The processing aids include 0.2-0.8% wetting and leveling agent, 0.5-2% crosslinking agent, and 0.1-0.5% defoamer, accounting for 0.2-0.8% of the total weight of the slurry. The final viscosity of the slurry is 3000-4000 cps.
[0007] Preferably, the CNC spraying platform in step three integrates a six-axis robotic arm and a piezoelectric inkjet printhead or an ultrasonic atomizing printhead. The printhead has an aperture of 0.15-0.25 mm and a spraying frequency of 10-30 kHz. In the non-contact quantitative spraying, the distance between the printhead and the fabric surface is 10-25 mm, the robotic arm moves at a speed of 0.3-0.8 m / s, and scanning is performed through a cross-spraying path. The amount of slurry deposited per unit area is controlled within the range of 60-120 g / m².
[0008] According to claim 1, the method for processing moxa wool is characterized in that the multi-temperature zone infrared pre-curing channel in step four includes at least three temperature zones: the first temperature zone has a temperature of 50-65℃ and an action time of 60-90 seconds; the second temperature zone has a temperature of 70-85℃ and an action time of 60-90 seconds; the third temperature zone has a temperature of 90-105℃ and an action time of 20-40 seconds; the moisture content of the fabric after pre-curing is reduced to 10-20%; the room temperature rolling treatment uses a rubber roller or silicone roller with a Shore A50-A70 hardness and a linear pressure of 20-40 N / cm.
[0009] Preferably, the final curing in step five is carried out in a hot air tenter frame at a curing temperature of 140-160℃ for 2-5 minutes. Under these conditions, the molecular chains in the composite matrix fully cross-link to form a dense three-dimensional network structure, which encapsulates and anchors all functional fillers. At the same time, some of the active ingredients of Artemisia argyi extract undergo graft copolymerization with the matrix to achieve a sustained-release function.
[0010] Preferably, the finishing process in step six specifically includes: first, subjecting the fabric to a gentle drying treatment at 100-130℃ for 2-4 minutes; then, performing a water-repellent finishing process using a padding method, with a padding rate of 65-75%, using fluorocarbon or silicon-carbon water-repellent agents, drying at 90-110℃, baking at 160-180℃, and baking for 50-70 seconds; the final forming process is laser cutting or ultrasonic sewing to produce a finished product of a specific shape from the fabric.
[0011] A functional mugwort fabric, characterized in that the fabric has a mugwort blended base and a functional composite coating permanently fixed on the base by chemical cross-linking; the functional composite coating is rich in ultrafine mugwort extract, far-infrared emitting materials and negative ion emitting materials.
[0012] Preferably, the 180° peel strength between the functional composite coating and the substrate is greater than 3 N / cm; after 20 standard washes, the visible appearance of the coating remains intact without peeling or damage, its far-infrared normal emissivity remains above 0.85, its negative ion emission remains above 1200 ions / cm³, and its active ingredient retention rate is above 80%; the fabric is non-irritating to human skin.
[0013] Application of functional mugwort floss fabric in products, the products being used to make bed sheets, duvet covers, pillowcases, towels, clothing, and quilt inserts.
[0014] The beneficial effects of this invention are: This application provides a method for processing mugwort floss, fabric, and related products, including a processing method of substrate pretreatment, slurry preparation, CNC spraying, gradient curing, and finishing. The substrate pretreatment optimizes the fiber surface state through cleaning and anti-oxidation treatment. The slurry preparation uses a composite base material of natural plant gum and synthetic resin, combined with ultrafine mugwort powder and inorganic functional fillers. The CNC spraying platform achieves quantitative deposition in specific areas through program control. Gradient curing enhances the coating bonding through the synergistic effect of temperature and mechanical force fields. The finishing process imparts a soft touch and water-repellent properties to the fabric. Three-dimensional cross-linking curing enhances the coating strength, and the composite functional slurry achieves multi-effect synergy, which has the advantages of improving the functional durability of the mugwort floss fabric, enhancing the coating bonding strength, and achieving precise functional area distribution. Attached Figure Description
[0015] To more clearly illustrate the technical solutions of the embodiments of this application, the accompanying drawings used in the embodiments will be briefly introduced below. It should be understood that the following drawings only show some embodiments of this application and should not be regarded as a limitation of the scope. For those skilled in the art, other related drawings can be obtained based on these drawings without creative effort.
[0016] Figure 1 This is a flowchart of the steps of the present invention. Detailed Implementation
[0017] To make the objectives, technical solutions, and advantages of the embodiments of this application clearer, the technical solutions of the embodiments of this application will be clearly and completely described below with reference to the accompanying drawings. Obviously, the described embodiments are only some embodiments of this application, and not all embodiments. The components of the embodiments of this application described and shown in the accompanying drawings can generally be arranged and designed in various different configurations.
[0018] Therefore, the following detailed description of the embodiments of this application provided in the accompanying drawings is not intended to limit the scope of the claimed application, but merely to illustrate selected embodiments of the application. All other embodiments obtained by those skilled in the art based on the embodiments of this application without inventive effort are within the scope of protection of this application.
[0019] It should be noted that similar labels and letters in the following figures indicate similar items. Therefore, once an item is defined in one figure, it does not need to be further defined and explained in subsequent figures.
[0020] In the description of this application, it should be noted that the terms "center," "upper," "lower," "left," "right," "vertical," "horizontal," "inner," and "outer," etc., indicate the orientation or positional relationship based on the orientation or positional relationship shown in the accompanying drawings, or the orientation or positional relationship commonly used when the product of this application is in use. They are only for the convenience of describing this application and simplifying the description, and do not indicate or imply that the device or element referred to must have a specific orientation, or be constructed and operated in a specific orientation, and therefore should not be construed as a limitation on this application. In addition, the terms "first," "second," and "third," etc., are only used to distinguish descriptions and should not be construed as indicating or implying relative importance.
[0021] Furthermore, terms such as "horizontal," "vertical," and "sag" do not imply that components must be absolutely horizontal or suspended, but rather that they can be slightly tilted. For example, "horizontal" simply means that its direction is more horizontal relative to "vertical," and does not mean that the structure must be completely horizontal, but can be slightly tilted.
[0022] In the description of this application, it should also be noted that, unless otherwise expressly specified and limited, the terms "set up," "install," "connect," and "link" should be interpreted broadly. For example, they can refer to a fixed connection, a detachable connection, or an integral connection; they can refer to a mechanical connection or an electrical connection; they can refer to a direct connection or an indirect connection through an intermediate medium; and they can refer to the internal connection of two components. Those skilled in the art can understand the specific meaning of the above terms in this application based on the specific circumstances.
[0023] like Figure 1 As shown, this application proposes a method for processing moxa wool, including the following steps: Step 1: Substrate pretreatment: Provide an wormwood blended fabric, and clean, anti-oxidize and perform conventional pretreatment on the fabric to achieve the preset wicking effect and pH value; Step 2, Slurry preparation: Prepare an aqueous composite functional slurry, which includes a composite base material composed of natural plant gum and aqueous synthetic resin, a functional filler containing ultrafine Artemisia argyi extract powder and inorganic functional powder, and processing aids; homogenize it and achieve the predetermined viscosity by a combination of high-speed stirring and ultrasonic dispersion. Step 3, Functional Artemisia argyi fabric spraying: Fix the fabric treated in Step 1 onto the CNC spraying platform, and control the precision nozzle to perform non-contact quantitative spraying on specific areas of the fabric according to the pre-designed digital pattern program, so as to accurately control the amount of slurry deposited per unit area. Step 4, Pre-curing and intermediate treatment: The sprayed fabric is subjected to gradient heating through a multi-temperature zone infrared pre-curing channel to allow the slurry to initially form a film and set. Then, a room temperature rolling process is performed to smooth the fibers and enhance adhesion. Step 5, Final Curing: The intermediate-treated fabric is fully cross-linked and cured in a high-temperature hot air environment, so that the slurry base material forms a three-dimensional network structure to permanently fix the functional filler. Step 6, Post-treatment: The cured fabric is subjected to gentle drying, water-repellent finishing and final molding to obtain functional moxa wool fabric products with enhanced functions.
[0024] This application proposes a processing method including substrate pretreatment, slurry preparation, CNC spraying, gradient curing, and finishing. The substrate pretreatment optimizes the fiber surface state through cleaning and anti-oxidation treatment. The slurry preparation uses a composite base of natural plant gum and synthetic resin, combined with ultrafine Artemisia argyi powder and inorganic functional fillers. The CNC spraying platform achieves quantitative deposition in specific areas through program control. Gradient curing enhances the coating bonding through the synergistic effect of temperature field and mechanical force field. Finishing imparts a soft touch and water-repellent properties to the fabric.
[0025] The process includes several key steps: Substrate pretreatment refers to chemically treating the fabric to achieve a specific surface-active state, typically through citric acid solution immersion combined with washing. This treatment removes fibrous impurities and creates a microstructure conducive to coating adhesion. Slurry preparation involves forming a stable, dispersed functional fluid material, often achieved using a high-speed shear emulsifier and an ultrasonic processor. This process ensures uniform dispersion of ultrafine powder and preserves active ingredients. The CNC spraying platform is a device with programmed positioning and deposition capabilities, typically using a six-axis robotic arm equipped with piezoelectric nozzles. This device achieves spatially selective distribution of functional materials through digital path planning. Gradient curing refers to a staged, temperature-controlled energy application method, often achieved using a multi-temperature zone infrared radiation device. This method avoids coating cracking caused by sudden temperature changes. (Functional moxa wool fabric) Specifically, after pretreatment, the fiber substrate develops a uniform micro-roughness and active groups on its surface, providing bonding sites for subsequent coatings. Natural plant gums and synthetic resins in the composite slurry form an interpenetrating network structure, generating a three-dimensional skeleton through cross-linking during the curing stage, encapsulating and fixing the mugwort powder and inorganic fillers. CNC spraying, based on a pre-set ergonomic model, increases the slurry deposition in corresponding acupoint areas, forming functionally enhanced zones. The pre-curing stage uses gradual heating to promote the initial extension of the slurry molecular chains, while room-temperature rolling eliminates fiber warping and enhances interfacial contact. The final curing stage uses high temperature to trigger the resin cross-linking reaction, forming an irreversible chemical bond structure. A water-repellent finish forms a low surface energy protective layer on the coating surface, balancing functionality and durability. Functional Mugwort Floss Fabric Compared to existing technologies, traditional processes using padding or coating result in uniform distribution of functional materials across the entire surface, while this solution achieves localized functional enhancement through programmed spraying. Traditional physical adsorption methods rely on mechanical locking within fiber pores, while this solution uses chemical cross-linking to form covalent bonds for anchoring. The traditional single function of moxa wool is expanded into a multi-effect synergistic system of far-infrared and negative ion generation. Functional moxa wool fabric. Through the above technical solutions, this application achieves selective enrichment of functional materials in the target area of the fabric, so that the mugwort components can be focused on specific parts of the human body; the functional components are permanently fixed on the fiber surface through a chemical cross-linking network, overcoming the defects of easy fall-off of physical adsorption; the synergistic effect of composite functional fillers enables the fabric to simultaneously possess the functions of mugwort activity release, far-infrared heat effect and negative ion air purification.
[0026] This application further proposes that the blending ratio of mugwort fiber to natural fiber in mugwort blended fabric is 50-70 / 50-30, and the antioxidant treatment is carried out by treating with citric acid or ascorbic acid solution at 3-8% concentration at 50-70℃ for 20-40 minutes. After conventional pretreatment, the fabric has a capillary effect ≥10cm / 30min, a pH value of 6.5-7.5, and a moisture content of less than 10%.
[0027] The blending ratio of velvet fiber and natural fibers refers to the mass percentage of the two fibers in the fabric. This can be achieved using a combed blending process, controlling the fiber ratio to give the fabric both flexibility and structural stability. The antioxidant treatment solution is a liquid treatment agent containing acidic components, achieved using a circulating impregnation process. This acidic environment removes impurities from the fiber surface and inhibits oxidation. Capillary effect is a quantitative indicator of the fabric's capillary effect, specifically tested using the vertical wicking method. Controlling pretreatment process parameters allows the liquid to form stable diffusion channels between fibers. pH value refers to the acidity or alkalinity of the fabric surface, achieved using a neutralization washing process. Adjusting the number of rinses and water quality ensures the chemical activity of the fiber surface reaches a preset range. Moisture content refers to the moisture content of the fabric after drying, achieved using a hot air drying process. Controlling the drying temperature and time ensures the fibers are moderately dry.
[0028] Specifically, when the blend ratio is limited to 50-70 / 50-30, the velvet fibers and natural fibers form an interwoven three-dimensional structure, enhancing the mechanical interlocking force between fibers while maintaining the fabric's softness. Treatment with a 3-8% concentration of citric acid or ascorbic acid solution at 50-70℃ decomposes impurities on the fiber surface under acidic conditions and avoids fiber embrittlement caused by high temperatures. A treatment time of 20-40 minutes balances cleaning effectiveness and energy efficiency. A capillary effect ≥10cm / 30min indicates that the fabric has good liquid conductivity, allowing subsequent sizing agents to penetrate evenly along the fiber gaps. When the pH value is controlled within the range of 6.5-7.5, the charge distribution on the fiber surface is conducive to the chemical adsorption of polar groups in the sizing agent. A moisture content below 10% prevents coating cracking caused by rapid evaporation of water during sizing agent spraying, while retaining trace amounts of hydroxyl groups on the fiber surface to enhance interfacial bonding.
[0029] Compared to existing technologies, traditional moxa wool fabrics often use single fibers or random blends, resulting in insufficient fiber bonding and easy delamination during subsequent processing. Existing antioxidant treatments often employ high-temperature, strong-alkali treatments, which remove impurities but damage the fibers. This solution constructs a stable fiber network by limiting the blend ratio, uses a medium-temperature acidic treatment to clean the fibers while protecting their mechanical properties, and combines this with the synergistic control of wicking effect and pH value to create interfacial properties in the fabric substrate that are conducive to sizing wetting and curing.
[0030] Through the above technical solutions, this application solves the problem of poor sizing adhesion in velvet blended fabrics caused by weak fiber bonding, and avoids the detachment of functional fillers caused by insufficient pretreatment. The synergistic effect of fiber blending ratio and antioxidant treatment enhances the stability of the substrate structure. Precise control of capillary effect and pH value ensures uniform spreading and chemical bonding of the sizing on the fiber surface. Moisture content management effectively prevents the generation of coating defects, providing a physicochemical basis for the long-term maintenance of subsequent functional coatings.
[0031] Specifically, the velvet fiber and natural fiber can be replaced with materials such as nylon and cotton.
[0032] This application further proposes that in the slurry preparation process, the composite base material is composed of natural plant gum and waterborne polyurethane resin in a dry weight ratio of 30-50:70-50. The natural plant gum is selected from one or more of guar gum, xanthan gum, and locust bean gum, and the waterborne synthetic resin is selected from one or more of waterborne polyurethane, waterborne acrylic resin, and waterborne epoxy resin. The functional filler includes ultrafine Artemisia argyi extract powder with a particle size of 800-1200 mesh, which accounts for 10-20% of the total weight of the slurry. The inorganic functional powder adopts nano- to submicron-sized far-infrared ceramic powder and negative ion mineral powder, which account for 3-8% of the total weight of the slurry, respectively. The processing aids include wetting and leveling agent (0.2-0.8% of the total weight of the slurry), crosslinking agent (0.5-2% of the total weight of the slurry), and defoamer (0.1-0.5% of the total weight of the slurry). The final viscosity of the slurry is controlled at 3000-4000 cps. Functional Artemisia argyi fabric The composite base material of natural plant gums and water-based synthetic resins refers to a synergistic film-forming system of bio-based materials and synthetic resins. Specifically, it can be achieved using a mixture of guar gum and water-based polyurethane. Natural plant gums provide biocompatibility and flexible support, while synthetic resins enhance mechanical strength and adhesion. The particle size control of ultrafine Artemisia argyi extract powder refers to the preparation of micron-sized active substances through airflow milling, specifically achieved using graded sieving technology. This particle size range ensures the dispersion and release efficiency of active ingredients in the slurry. The compounding of inorganic functional powders refers to the combination of far-infrared ceramic powder and negative ion minerals. Specifically, it can be achieved using a blend system of zirconate ceramics and tourmaline powder, which respectively generate thermal effects and air purification functions. The gradient addition of processing aids refers to the introduction of auxiliary components in stages according to functional requirements. Wetting and leveling agents can be polyether-modified siloxanes, crosslinking agents can be aziridine compounds, and defoamers can be mineral oil-based emulsions. Precise control of slurry performance is achieved through sequential addition. Functional Artemisia argyi fabric. Specifically, an interpenetrating network structure is formed through a composite base of natural plant gums and synthetic resins. During the curing process, the hydroxyl groups of the plant gums react with the isocyanate groups of the resins to form a three-dimensional cross-linked system that combines flexibility and strength. After ultrafine Artemisia argyi powder is uniformly dispersed in the slurry, its surface-active components and inorganic powders undergo synergistic adsorption through van der Waals forces, forming stable functional units in the coating. A wetting and leveling agent reduces the surface tension of the slurry, allowing it to fully wet the fiber surface; a cross-linking agent initiates cross-linking reactions between molecular chains during the pre-curing stage; and an antifoaming agent eliminates bubbles generated by high-speed stirring. Finally, viscosity control ensures that the slurry maintains stable rheological properties during spraying. Functional Artemisia argyi fabric. Compared to existing technologies, traditional slurries often use a single resin base, resulting in insufficient coating flexibility and easy detachment of active ingredients. In existing technologies, inorganic fillers are typically mixed mechanically, which easily leads to agglomeration and sedimentation. This solution, however, uses particle size matching and surface modification to create a stable suspension system of different functional fillers in the slurry. Existing slurry additives are often added in excess, affecting film-forming performance. This solution optimizes the efficiency of additives through a gradient addition design. Functional Artemisia argyi fabric. Through the above technical solutions, this application achieves precise compatibility of slurry components, solves the problem of insufficient coating adhesion, avoids the agglomeration of functional fillers, and improves the processing stability of the slurry. The synergistic effect of natural components and synthetic materials enables the coating to possess both bioactivity and durability, the uniform dispersion of inorganic functional fillers enhances the synergistic release of multi-functional properties, and the optimized design of the additive system ensures the applicability of the slurry in precision spraying processes.
[0033] This application further proposes that the CNC spraying platform in step three integrates a six-axis robotic arm and a piezoelectric inkjet printhead or an ultrasonic atomizing printhead. The printhead has an aperture of 0.15-0.25 mm and a spraying frequency of 10-30 kHz. In the non-contact quantitative spraying, the distance between the printhead and the fabric surface is 10-25 mm, the robotic arm moves at a speed of 0.3-0.8 m / s, and scanning is performed through a cross-spraying path. The amount of slurry deposited per unit area is controlled within the range of 60-120 g / m².
[0034] Among them, a six-axis robotic arm refers to an industrial robot system with six degrees of freedom, specifically implemented using a serial multi-joint structure. It can achieve multi-angle positioning in three-dimensional space, providing motion support for the complex trajectory of the spraying path. A piezoelectric inkjet printhead is a device that uses the deformation of piezoelectric ceramics to generate pulse pressure to achieve droplet ejection. An ultrasonic atomizing printhead is a device that breaks liquid into micron-sized droplets through high-frequency vibration. Both can adjust droplet size and ejection frequency by controlling drive signals. Cross-spraying paths refer to the coverage trajectory formed by the printhead moving alternately along the transverse and longitudinal directions on the fabric surface. This can be achieved using a gridded scanning mode to eliminate striped distribution defects caused by unidirectional spraying. Slurry deposition control refers to adjusting the printhead flow rate, moving speed, and number of scans to achieve a predetermined threshold for slurry coverage per unit area. This can be achieved by using a closed-loop feedback system to monitor coating thickness in real time.
[0035] Specifically, a six-axis robotic arm drives a nozzle to move along a preset trajectory on the fabric surface. Piezoelectric or ultrasonic atomizing nozzles atomize the slurry into micron-sized droplets, which are then sprayed onto the target area. The combination of nozzle orifice diameter and spray frequency controls the atomized particle size, preventing uneven fiber wetting caused by excessively large droplets. A spraying distance of 10-25mm prevents slurry scattering while ensuring sufficient spread of atomized droplets. The combination of the robotic arm's 0.3-0.8m / s movement speed and intersecting paths allows the slurry to form a continuous and uniform coating during dynamic deposition. A deposition rate range of 60-120g / m², achieved through precise control of spraying parameters, satisfies the effective load of functional fillers while preventing excessive slurry from clogging fiber gaps. This combined technology allows the slurry to form a directional functional layer only in designated areas of the fabric, rather than the full-width coverage of traditional processes.
[0036] Compared to existing technologies, traditional moxa wool fabrics use impregnation or coating processes to achieve functional layer adhesion, resulting in indiscriminate coverage of the slurry on the fiber surface and an inability to provide targeted reinforcement to acupoints. This solution, however, utilizes the spatial positioning capabilities of a CNC spraying platform, combined with high-frequency atomization and dynamic deposition control, to achieve selective construction of the functional coating. Existing technologies lack coordinated adjustment between nozzle movement speed and slurry flow rate, leading to coating thickness fluctuations. This solution, through cross-path scanning and closed-loop control of deposition volume, significantly improves coating uniformity. Furthermore, existing physical adhesion methods are prone to filler detachment due to mechanical friction. This solution reduces fiber damage through non-contact spraying, creating conditions for subsequent curing and the formation of chemical bonds.
[0037] Through the above technical solutions, this application achieves precise positioning and deposition of the slurry in specific areas of the fabric, concentrating the functional filler in the target area and avoiding ineffective dispersion. The synergistic effect of high-frequency atomization and dynamic spraying parameters ensures uniform thickness of the functional layer and tight bonding with the fibers, solving the problem of poor physical adhesion. Cross-path scanning eliminates the trajectory overlap defects of unidirectional spraying, improving the surface smoothness of the coating. Non-contact operation reduces physical impact on the fiber structure, maintaining the flexibility of the substrate while providing a uniform slurry distribution foundation for subsequent curing to form a stable three-dimensional network.
[0038] This application further proposes that in the pre-curing and intermediate treatment steps, the multi-temperature zone infrared pre-curing channel includes at least three temperature zones: the first temperature zone is 50-65℃, with an action time of 60-90 seconds; the second temperature zone is 70-85℃, with an action time of 60-90 seconds; and the third temperature zone is 90-105℃, with an action time of 20-40 seconds. After pre-curing, the moisture content of the fabric is reduced to 10-20%. The room temperature rolling treatment uses rubber or silicone rollers with a Shore A50-A70 hardness and a linear pressure of 20-40 N / cm. Functional moxa wool fabric. The multi-temperature zone infrared pre-curing channel refers to a heating device containing three independent temperature control sections. This can be achieved through a segmented infrared radiation plate linked with temperature sensors, gradually evaporating moisture from the slurry and promoting the orderly arrangement of the base material molecular chains via gradient heating. The moisture content after pre-curing is controlled at 10-20%, meaning that infrared heating allows the fabric to retain some moisture during the curing process. This can be achieved using an online moisture content meter and dynamic adjustment of temperature zone parameters. This moisture content range maintains appropriate fiber plasticity to support subsequent rolling processing. The room-temperature rolling process uses elastic rollers with a Shore A50-A70 hardness, meaning rollers made of rubber or silicone with a certain deformation capacity. This can be achieved by adjusting the degree of rubber vulcanization or the crosslinking density of silicone. This hardness range ensures uniform pressure transmission and avoids damage to the pre-cured coating. The linear pressure of 20-40 N / cm refers to the mechanical pressure applied per unit length of the roller. This can be achieved through a pneumatic pressure regulation system or servo motor control of the roller spacing. This pressure range eliminates micro-undulations on the fiber surface and enhances the mechanical adhesion between the coating and the substrate. Functional moxa wool fabric Specifically, in the pre-curing stage, the slurry first undergoes slow evaporation of moisture in a low-temperature zone to prevent the formation of pores within the coating due to rapid evaporation; then, in a medium-temperature zone, the molecular chains of the base material are initially extended, forming local cross-linking points; finally, in a high-temperature zone, the surface layer is rapidly shaped to lock in the distribution of functional fillers. Through staged temperature control, the internal structure of the slurry is gradually densified, while avoiding coating cracking caused by sudden temperature changes. The moisture content retained after pre-curing provides the necessary plasticity for rolling processing, allowing the fibers to deform appropriately under pressure to fill the gaps between the coating and the substrate. During room-temperature rolling, the elastic rollers apply uniform pressure to create a mechanical interlocking structure between the fibers and the coating, while preventing the pre-cured layer from cracking due to excessive pressure. Functional Wool Fabric Compared to existing technologies, traditional curing processes typically employ a single temperature zone or a simple two-stage heating method, leading to premature hardening of the slurry surface and a loose internal structure. Existing rolling processes often use hard metal rollers, which can easily cause fiber damage or coating peeling. This solution achieves simultaneous improvement in coating internal structure homogenization and interfacial adhesion through the synergistic effect of three-temperature zone gradient heating and elastic roller pressing. Functional moxa wool fabric Through the above technical solutions, this application solves the problem of insufficient adhesion caused by the loose structure during the initial curing of the slurry, while balancing the contradiction between processing efficiency and coating physical properties. The gradient heating strategy shortens the curing cycle while ensuring film integrity, while the elastic rolling process enhances the coating adhesion and avoids fiber damage, ultimately obtaining a functional coating with a dense structure and stable adhesion.
[0039] This application further proposes final curing in a hot air tenter frame, with the curing temperature controlled at 140-160℃ and the curing time controlled at 2-5 minutes. Under these conditions, the molecular chains in the composite matrix fully cross-link to form a dense three-dimensional network structure, encapsulating and anchoring all functional fillers. Simultaneously, some of the active ingredients from the Artemisia argyi extract undergo graft copolymerization with the matrix to achieve a sustained-release function. Functional Artemisia argyi fabric. Among them, the hot air tenter frame refers to a hot air circulation device with lateral stretching function. Specifically, a tenter frame with a temperature gradient control system can be used, ensuring uniform heating of the fabric through uniform hot air distribution. The curing temperature range of 140-160℃ refers to the optimal temperature range for the resin base material to undergo cross-linking reaction. This can be precisely controlled through a PID temperature control module, activating the resin's cross-linking reaction while avoiding damage to the active components of Artemisia argyi. The three-dimensional network structure refers to a three-dimensional network morphology formed by the cross-linking of molecular chains. Specifically, it is formed through the condensation reaction of active groups in water-based synthetic resin at high temperatures. Its mesh size is smaller than the particle size of the functional filler, thus achieving physical anchoring. The graft copolymerization reaction refers to the chemical bonding between the active hydroxyl groups in Artemisia argyi extract and the isocyanate groups on the resin molecular chains. Specifically, by controlling the curing time, some active components participate in the reaction to form covalent bonds. Functional Artemisia argyi fabric. Specifically, during the hot air stretching and setting process, the fabric is uniformly heated to a set temperature range, causing the molecular chains of the water-based synthetic resin in the composite matrix to begin moving. When the temperature reaches above the glass transition temperature of the resin, the active groups between the molecular chains undergo a condensation reaction, gradually forming a continuous three-dimensional network through the formation of cross-linking points. During this process, inorganic functional fillers such as far-infrared ceramic powder and negative ion mineral powder are encapsulated within the network pores, forming a mechanically interlocked structure. Simultaneously, the active ingredients in the Artemisia argyi extract undergo physical adsorption with the resin matrix through intermolecular forces. Some of the active substances containing hydroxyl groups undergo grafting reactions with the isocyanate groups of the resin, forming stable chemical bonds. This dual fixation mechanism ensures both the permanent fixation of the functional fillers and the slow release of unreacted active ingredients through the porous structure of the three-dimensional network. Functional Artemisia argyi fabric. Compared to existing technologies, traditional mugwort fabrics use physical impregnation or spraying to fix the mugwort components, relying solely on capillary action or van der Waals forces on the fiber surface for adhesion, which easily leads to detachment during washing or friction. This solution, however, utilizes a three-dimensional network structure formed by chemical cross-linking, completely encapsulating the functional filler within the mesh created by the cross-linking points, resulting in a bonding strength two orders of magnitude higher than physical adsorption. Existing technologies largely depend on coating thickness control for active ingredient release, failing to achieve sustained release. This solution, through the synergistic effect of chemical bonding points formed by graft copolymerization and the diffusion channels of unreacted active ingredients, reduces the release rate by approximately 60%. Functional Mugwort Fabric Through the above technical solution, this application effectively solves the problem of poor adhesion caused by the physical adhesion of Artemisia argyi extract. It achieves permanent fixation of functional fillers through a chemical cross-linking network, increasing the coating peel strength to more than three times that of traditional processes. Simultaneously, a sustained-release mechanism for active ingredients is established, maintaining over 80% retention of effective ingredients after 20 standard washes, giving the fabric continuous functional release characteristics. The three-dimensional network structure also enhances the mechanical stability of the coating, preventing cracking or powdering during use.
[0040] This application further proposes post-processing specifically including: firstly, a gentle drying treatment of the fabric at 100-130℃ for 2-4 minutes; subsequently, a water-repellent finishing process using a padding method, with a padding rate of 65-75%, using fluorocarbon or silicon-carbon water-repellent agents, a drying temperature of 90-110℃, a baking temperature of 160-180℃, and a baking time of 50-70 seconds; the final shaping process involves laser cutting or ultrasonic sewing to create end products of specific shapes. Functional Moxa Wool Fabric Among these processes, gentle drying refers to the mild drying of fabrics within a specific temperature range, which can be achieved using a circulating hot air system. This step effectively removes residual moisture while avoiding damage to the fiber structure caused by high temperatures. Padding-type water-repellent finishing involves applying a finishing agent through immersion and roller pressing, which can be achieved using a three-roller padding machine. Controlling the padding rate ensures that the finishing agent penetrates evenly into the fiber gaps. Fluorocarbon or silicon-carbon water-repellent agents refer to fluoropolymers or organosilicon compounds, which can be achieved using perfluoroalkyl acrylate copolymers or polysiloxane emulsions. Their low surface energy characteristics enhance the hydrophobicity of the coating. Laser cutting refers to non-contact cutting using a high-energy beam, which can be achieved using a carbon dioxide laser. Precise control of the spot diameter and movement path avoids damage to the functional coating. Ultrasonic stitching refers to fusing fibers through high-frequency mechanical vibration, which can be achieved using a combination of piezoelectric transducers and titanium alloy welding heads. This method forms a strong seam without traditional sewing thread. Functional moxa wool fabric. Specifically, the soft-drying stage maintains fiber morphological stability through precise temperature control, providing a smooth substrate for subsequent finishing; the optimized roll-off rate in the padding process ensures that the water-repellent agent fully penetrates the fiber interior rather than merely adhering to the surface; the step-by-step drying and baking processes, through gradient temperature increases, promote the chemical bonding between the finishing agent and the substrate, thereby improving the durability of the waterproof effect; laser cutting, through a non-contact processing mode, avoids coating peeling caused by mechanical stress, and ultrasonic stitching achieves seamless connection through localized heat fusion; both work together to ensure the structural integrity of the functional composite layer. All process parameters are systematically matched to ensure the stable fixation of functional components while achieving precise molding of the final product. Functional moxa wool fabric. Compared to existing technologies, traditional moxa wool fabrics often rely on a single hot air drying process, leading to fiber embrittlement. This solution, however, effectively protects fiber strength through staged temperature-controlled gentle drying. Conventional padding processes, lacking controlled roll-in rates, easily cause uneven distribution of finishing agents. This solution optimizes the roll-in rate range to achieve effective penetration of functional additives. Existing product molding relies heavily on mechanical cutting and sewing, easily causing coating edge cracking. This solution uses non-contact processing technology to avoid physical damage. Traditional water-repellent finishing often uses a single high-temperature treatment. This solution strengthens interfacial adhesion through step-by-step drying and baking. Functional Moxa Wool Fabric Through the above technical solution, this application achieves a durable bond between the functional coating and the substrate, significantly improves the washability of the waterproof performance, effectively avoids coating damage during processing, and ensures precise control of the final product form, thus solving the technical defects of traditional velvet fabric functional materials such as easy detachment, poor durability, and insufficient molding precision.
[0041] This application further proposes a functional mugwort fabric comprising a mugwort blended base and a functional composite coating permanently fixed by chemical cross-linking. The composite coating contains ultrafine mugwort extract, far-infrared emitting materials, and negative ion emitting materials. Functional Mugwort Fabric The moxa wool blended substrate refers to a porous substrate formed by blending moxa wool fibers with natural fibers in a specific ratio. The fiber spacing can be optimized by adjusting the blending ratio, providing physical anchoring points for subsequent coating penetration. Chemical cross-linking permanent fixation refers to the formation of a three-dimensional network structure through a cross-linking agent under high-temperature curing conditions. Specifically, a composite base material of water-based synthetic resin and natural plant gum is used to achieve stable coating of functional fillers. The functional composite coating is a surface treatment layer containing multiple functional components, specifically achieving multiple health benefits through the synergistic combination of ultrafine moxa leaf extract and inorganic powder. Functional moxa wool fabric. Specifically, the mugwort-blend base layer forms a porous structure through fiber blending, allowing the coating slurry to penetrate into the fiber gaps and enhance interfacial adhesion. During the chemical cross-linking process, the composite base material forms a dense three-dimensional network structure at high temperatures, permanently anchoring ultrafine mugwort extract, far-infrared ceramic powder, and negative ion mineral powder to the base surface. In the functional composite coating, the ultrafine mugwort extract releases active ingredients through a slow-release effect, the far-infrared material promotes local blood circulation through thermal radiation, and the negative ion material improves the air ion environment through charge distribution. The three work synergistically to achieve a composite health-care function. Functional mugwort fabric Compared to existing technologies, traditional moxa wool fabrics rely on physical methods to attach moxa wool, resulting in uniform distribution but lacking directional application and prone to detachment. This solution achieves directional deposition and permanent fixation of the coating through a combination of a porous substrate structure and chemical cross-linking. Furthermore, it overcomes the limitations of single-function applications through the composite design of functional fillers. Existing technologies do not address the synergistic application of inorganic functional materials and moxa leaf components, while this solution achieves multiple functionalities through material selection and structural design. Functional Moxa Wool Fabric Through the above technical solution, this application solves the problems of moxa wool fabric's inability to target specific areas, low adhesion, and limited functionality. The combination of the porous substrate and chemical cross-linking allows the coating to be precisely positioned, deposited, and firmly adhered, preventing detachment. The synergistic effect of different functional materials in the composite coating achieves integrated functions of sustained release of moxa activity, far-infrared thermal effect, and negative ion environment regulation, breaking through the limitations of a single health care model. The three-dimensional network structure of the coating effectively protects the functional components, ensuring long-term stability.
[0042] This application further proposes that the functional composite coating has a 180-degree peel strength greater than 3 N / cm between itself and the substrate, and that the coating shows no visible damage or peeling after 20 standard washes. Its far-infrared normal emissivity remains above 0.85, its negative ion emission remains above 1200 ions / cm³, its active ingredient retention rate is above 80%, and the fabric is non-irritating to human skin.
[0043] Among them, 180-degree peel strength refers to the coating's resistance to separation from the substrate in a vertical peel test. This can be achieved by adjusting the crosslinking agent content in the slurry and the high-temperature curing process parameters. The crosslinking agent promotes the formation of a three-dimensional crosslinked network of the substrate molecular chains. Appearance integrity after standard washing refers to the structural stability of the coating under mechanical friction and chemical detergent action. This can be achieved by optimizing the gradient heating program in the pre-curing stage and room-temperature rolling treatment. Gradient heating allows the slurry to gradually form and solidify into a film. Far-infrared normal emissivity refers to the material's ability to radiate far-infrared rays in the normal direction. This can be achieved by controlling the particle size distribution of inorganic functional powders and the anchoring effect of the substrate on the powders. Nanoscale powders have higher surface activity. Negative ion emission refers to the number of negative ions released per unit volume of air. This can be achieved by designing the crystal structure of negative ion mineral powders and ensuring the uniformity of slurry dispersion. Crystal defects generate an electrostatic field that promotes air ionization. Active ingredient retention rate refers to the degree to which the effective components of Artemisia argyi extract are retained during processing and use. This can be achieved through the grafting reaction of natural plant gums with active ingredients and the slow-release structure. The plant gum molecular chains form a coating barrier. Non-irritating to the skin means that the material meets the requirements of biocompatibility, which can be achieved by controlling the types of additives and removing residues in the pretreatment process, using non-toxic cross-linking agents and setting up sufficient post-treatment processes.
[0044] Specifically, a dense three-dimensional network structure is formed between the coating and the substrate through chemical cross-linking, maintaining interfacial adhesion under mechanical stress and preventing physical detachment. During washing, the cross-linked network anchors the functional fillers, preventing the loss of inorganic powder, while the coating structure of the base material slows down the dissolution of active ingredients from Artemisia argyi extract. The durability of far-infrared and negative ion functions depends on the uniform dispersion and chemical bonding state of inorganic powder in the base material; nano-sized powder enhances the persistence of function through surface effects. Skin contact safety is ensured through dual guarantees of raw material screening and process control, eliminating toxic monomer residues and removing irritating substances from the fiber surface.
[0045] Compared to existing technologies, traditional mugwort fabrics, which use physical mixing methods, result in uneven distribution of functional components and are prone to falling off. This solution, however, achieves permanent fixation of the functional fillers through chemical cross-linking, while integrating far-infrared rays, negative ions, and mugwort components to form a composite functional layer. Existing products experience functional degradation after multiple washes; this solution maintains functional stability through a base material network structure design, overcoming the limitations of single health-care functions.
[0046] Through the above technical solutions, this application effectively solves the problems of easy coating peeling, loss of functional components and poor durability, ensuring that the functional composite coating maintains stable physical bonding strength and functional output during long-term use, while meeting the safety requirements for direct skin contact, and providing reliable technical support for the development of textile products with multiple health care functions.
[0047] This application further proposes the application of functional moxa wool fabric in the production of bed sheets, duvet covers, pillowcases, towels, clothing, and comforter inserts. Functional moxa wool fabric Bed sheets, duvet covers, pillowcases, towels, clothing, and quilt inserts refer to intimate textiles that come into direct contact with the skin, and can be produced using conventional textile cutting and sewing techniques. These products cover specific areas of the body, allowing the functional materials in the fabric to maintain continuous contact with the target areas, thereby achieving targeted release of health benefits. The functional composite coating refers to a functional layer permanently fixed to an mugwort blended base through chemical cross-linking, specifically achieved using a spray-curing process. This coating contains ultrafine mugwort extract, far-infrared ceramic powder, and negative ion mineral powder, enhancing the health benefits through the synergistic effect of multiple materials. Functional mugwort fabric. Specifically, in large-sized products such as bed sheets and duvet covers, the functional composite coating is applied to areas in contact with the back and neck, utilizing prolonged contact to promote the penetration of active ingredients from mugwort and the accumulation of far-infrared thermal effects. In small-sized products such as pillowcases and towels, the coating is concentrated on areas in contact with the head and face, accelerating the release of negative ions through high-frequency wiping. In clothing, the coating is precisely applied to areas corresponding to acupoints, enhancing the material's effectiveness through friction generated by body movement. Through these application methods, the distribution pattern of the functional materials matches ergonomic requirements, avoiding the energy dispersion problem caused by uniform coating. Simultaneously, the chemically cross-linked and fixed coating structure can withstand washing and mechanical forces, ensuring that the functional materials do not peel off during long-term use. Functional Mugwort Fabric Compared to existing technologies, traditional mugwort fabrics only disperse mugwort components throughout the fabric through physical mixing, failing to provide targeted functional enhancements for different parts of the body, and are prone to component loss during washing. This solution, by limiting the type of end product and its usage scenarios, adapts the distribution density and intensity of functional materials to the health needs of specific areas of the body. Simultaneously, it utilizes chemical bonding technology to improve coating durability, overcoming the technical shortcomings of traditional technologies such as limited functionality and material detachment. Functional Mugwort Fabric Through the above technical solution, this application achieves the precise release of the health care function of moxa wool in key parts of the human body, prolongs the effective action time of functional materials, and enhances the comprehensive performance of health care function through the synergistic effect of multiple materials.
[0048] The above are merely preferred embodiments of this application and are not intended to limit this application. Various modifications and variations can be made to this application by those skilled in the art. Any modifications, equivalent substitutions, improvements, etc., made within the spirit and principles of this application should be included within the protection scope of this application.
Claims
1. A method for processing mugwort floss, characterized in that, Includes the following steps: Step 1: Substrate pretreatment: Provide an wormwood blended fabric, and clean, anti-oxidize and perform conventional pretreatment on the fabric to achieve the preset wicking effect and pH value; Step 2, Slurry preparation: Prepare an aqueous composite functional slurry, which includes a composite base material composed of natural plant gum and aqueous synthetic resin, a functional filler containing ultrafine Artemisia argyi extract powder and inorganic functional powder, and processing aids; homogenize it and achieve the predetermined viscosity by a combination of high-speed stirring and ultrasonic dispersion. Step 3, Functional Artemisia argyi fabric spraying: Fix the fabric treated in Step 1 onto the CNC spraying platform, and control the precision nozzle to perform non-contact quantitative spraying on specific areas of the fabric according to the pre-designed digital pattern program, so as to accurately control the amount of slurry deposited per unit area. Step 4, Pre-curing and intermediate treatment: The sprayed fabric is subjected to gradient heating through a multi-temperature zone infrared pre-curing channel to allow the slurry to initially form a film and set. Then, a room temperature rolling process is performed to smooth the fibers and enhance adhesion. Step 5, Final Curing: The intermediate-treated fabric is fully cross-linked and cured in a high-temperature hot air environment, so that the slurry base material forms a three-dimensional network structure to permanently fix the functional filler. Step 6, Post-treatment: The cured fabric is subjected to gentle drying, water-repellent finishing and final molding to obtain functional moxa wool fabric products with enhanced functions.
2. The method for processing mugwort floss according to claim 1, characterized in that, In step one, the blending ratio of mugwort fibers to natural fibers in the mugwort blended fabric is (50-70) / (50-30). The antioxidant treatment uses a 3-8% citric acid or ascorbic acid solution at 50-70℃ for 20-40 minutes. After conventional pretreatment, the fabric has a capillary effect ≥10cm / 30min, a pH value of 6.5-7.5, and a moisture content of less than 10%.
3. The method for processing moxa wool according to claim 1, characterized in that, In step two, the dry weight ratio of natural plant gum to waterborne polyurethane resin in the composite base material is (30-50):(70-50). The natural plant gum is selected from one or more of guar gum, xanthan gum, and locust bean gum. The waterborne synthetic resin is selected from one or more of waterborne polyurethane, waterborne acrylic resin, and waterborne epoxy resin. The particle size of the ultrafine Artemisia argyi extract powder in the functional filler is 800-1200 mesh, accounting for 10-20% of the total weight of the slurry. The inorganic functional powder is far-infrared ceramic powder and negative ion mineral powder, with a particle size of nano to submicron, accounting for 3-8% of the total weight of the slurry, respectively. The processing aids include 0.2-0.8% wetting and leveling agent, 0.5-2% crosslinking agent, and 0.1-0.5% defoamer, accounting for 0.2-0.8% of the total weight of the slurry. The final viscosity of the slurry is 3000-4000 cps.
4. The method for processing mugwort floss according to claim 1, characterized in that, The CNC spraying platform described in step three integrates a six-axis robotic arm and a piezoelectric inkjet printhead or an ultrasonic atomizing printhead. The printhead has an aperture of 0.15-0.25 mm and a spraying frequency of 10-30 kHz. In the non-contact quantitative spraying, the distance between the printhead and the fabric surface is 10-25 mm, the robotic arm moves at a speed of 0.3-0.8 m / s, and scanning is performed through a cross-spraying path. The amount of slurry deposited per unit area is controlled within the range of 60-120 g / m².
5. The method for processing mugwort floss according to claim 1, characterized in that, The multi-temperature zone infrared pre-curing channel in step four includes at least three temperature zones: the first temperature zone is 50-65℃, and the action time is 60-90 seconds; the second temperature zone is 70-85℃, and the action time is 60-90 seconds; the third temperature zone is 90-105℃, and the action time is 20-40 seconds; after pre-curing, the moisture content of the fabric is reduced to 10-20%; the room temperature rolling treatment uses a rubber roller or silicone roller with a Shore A50-A70 hardness and a linear pressure of 20-40 N / cm.
6. The method for processing mugwort floss according to claim 1, characterized in that, The final curing described in step five is carried out in a hot air tenter frame at a curing temperature of 140-160℃ for 2-5 minutes. Under these conditions, the molecular chains in the composite matrix fully cross-link to form a dense three-dimensional network structure, which encapsulates and anchors all functional fillers. At the same time, some of the active ingredients of Artemisia argyi extract undergo a graft copolymerization reaction with the matrix to achieve a sustained-release function.
7. The method for processing mugwort floss according to claim 1, characterized in that, The finishing process described in step six specifically includes: first, subjecting the fabric to a gentle drying treatment at 100-130℃ for 2-4 minutes; then, performing a water-repellent finishing process using a padding method, with a padding rate of 65-75%, using fluorocarbon or silicon-carbon water-repellent agents, drying at 90-110℃, baking at 160-180℃, and baking for 50-70 seconds; the final forming process involves laser cutting or ultrasonic sewing to create a finished product of a specific shape from the fabric.
8. A functional moxa wool fabric prepared by the method described in any one of claims 1 to 7, characterized in that, The fabric has an artemisia-blend base and a functional composite coating permanently fixed to the base by chemical cross-linking; the functional composite coating is rich in ultrafine artemisia extract, far-infrared emitting materials and negative ion emitting materials.
9. The functional moxa wool fabric as described in claim 8, characterized in that, The functional composite coating has a 180° peel strength greater than 3 N / cm with the substrate; after 20 standard washes, the visible appearance of the coating remains intact without any damage or peeling; its far-infrared normal emissivity remains above 0.85; its negative ion emission remains above 1200 ions / cm³; and its active ingredient retention rate is above 80%; the fabric is non-irritating to human skin.
10. The application of the functional moxa wool fabric as described in claim 8 or 9 in the product, characterized in that, The product is used to make bed sheets, duvet covers, pillowcases, towels, clothes, and comforter inserts.
